Biology of Locastra muscosalis Walker (Lepidoptera : Pyralidae) a Defoliating Pest of Pistacia integerrima Stew Ex. Brandis - Sharma, Ajay; Verma, T. D. (Indian Forester, 2004)
Pistacia integerrima is a tree of great economic importance because of its ornamental and medicinal values and as its wood is used for making furniture. The defoliation caused in this tree hampers the production ofthe leaf galls formed on this tree which are capable of curing various diseases. Out of different defoliators, Locastrti muscosalis is the most important one which takes heavy toll of the foliage. This pests is reported for the first time on this tree. It is gregarious pest which live on the tree by making webs and is capable of defoliating the whole tree. The eggs are laid in the last week of June. 1st, 2nd and 3rd instar larvae are gregarious in hebaviour, but in the 4th and 5th instar the larvae change to solitary hebaviour. Larvae hibernate inside the silken cocoon from September onwards upto next June when pupation take place inside the cocoons made for hibernation. The black coloured adults with greenish tinge emerge in last week of June. Its detailed biology is being reported.